Notes on the Rhyacophila scissa species group with description of two new taxa from China (Trichoptera, Rhyacophilidae) - Sun, Chang-Hai (Zootaxa, 2016)
One new species, R. meniscoides n. sp., and 1 new subspecies, R. morsei concaviuscula n. sp., are described, diagnosed and illustrated. Two diagnostic species complexes within the R. scissa Species Group, the R. scissa Diagnostic Species Complex and the R. schismatica Diagnostic Species Complex, are recognized and delimited. The 15 previously described species and 1 new species and 1 new subspecies described in this article are assigned to the complexes accordingly. Distribution maps of all 17 members in the Species Group are presented.